An overview of scheduled wastes management in Malaysia - Hassan, Noor Artika; Yusof, Muhammad Zubir; Mohd Tohit, Nor Faiza (Zibeline International Publishing, 2019)
The article reviews the scheduled waste management in Malaysia. It describes the scheduled waste classifications, characteristics, the sources of scheduled wastes, the policies and regulations related to scheduled wastes, the management of scheduled wastes in Malaysia and the challenges related to scheduled waste management in Malaysia. Currently, the manufacturing industry has contributed the highest scheduled waste production in Malaysia. Under the Environmental Quality Act (EQA) 1974, the government has set up several legal provisions specifically for scheduled waste generation, storage, transportation, and disposal. The aims are to reduce the potential risks to human and the environment. The paradigm shift from cradle to grave to cradle to cradle concept is a sustainable and sound concept which is inevitable step to minimize the scheduled waste generation in Malaysia.